PLLA Honeycomb-Like Pattern on Fluorinated Ethylene Propylene as a Substrate for Fibroblast Growth - Fajstavrová, Klára; Rimpelová, Silvie; Fajstavr, Dominik; Švorčík, Václav; Slepička, Petr (Polymers, 2020)
In this study, we present the surface patterning of a biopolymer poly(l-lactide) (PLLA) for fibroblast growth enhancement. The patterning is based on a self-organized pore arrangement directly fabricated from a ternary system of a solvent-nonsolvent biopolymer. We successfully created a porous honeycomb-like pattern (HCP) on a thermally resistant polymer-fluorinated ethylene propylene (FEP). An important preparation step for HCP is activation of the substrate in Ar plasma discharge. The polymer activation leads to changes in the surface chemistry, which corresponds to an increase in the substrate surface wettability. The aim of this study was to evaluate the influence of the PLLA concentration in solution on the surface morphology, roughness, wettability, and chemistry, and subsequently, also on fibroblast proliferation. We confirmed that the amount of PLLA in solution significantly affects the material surface properties. The pore size of the prepared layers, the surface wettability, and the surface oxygen content increased with an increasing amount of biopolymer in the coating solution. The optimal amount was 1 g of PLLA, which resulted in the highest number of cells after 6 days from seeding; however, all three biopolymer concentrations exhibited significantly better results compared to pristine FEP. The cytocompatibility tests showed that the HCP promoted the attachment of cell filopodia to the underlying substrate and, thus, significantly improved the cell-material interactions. We prepared a honeycomb biodegradable support for enhanced cell growth, so the surface properties of perfluoroethylenepropylene were significantly enhanced.
Keywords: scaffold for cell culture; cell response; poly(l-lactic) acid; honeycomb film; fluorinated polymer; surface morphology